1983
DOI: 10.1071/bi9830251
|View full text |Cite
|
Sign up to set email alerts
|

Integumental Chitin Synthase Activity in Cell-free Extracts of Larvae of the Australian Sheep Blowfly, Lucilia cuprina, and Two Other Species of Diptera

Abstract: Chitin synthase activity has been demonstrated in crude homogenates of larval integuments from L. cuprina and in similar preparations from Musca domestica and Calliphora erythrocephala. This is the first report of an insect integumental chitin synthase. This activity brings about the incorporation of radioactivity from UDP-N-acetyl-[14C]glucosamine into an ethanol-and alkali-insoluble form. A major part of this labelled product has been characterized as chitin by its insolubility in alkali, resistance to degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Cohen and Casida (1982), for instance, reported different effects of polyoxins and nikkomycin on chitin synthesis in cecropia moth Hyalophora cecropia and cabbage looper Trichoplusia ni. Mayer et al (1980Mayer et al ( , 1981 observed polyoxin D inhibition in microsomal preparations from Stomoxys only at high concentrations but no inhibitory effect for diflubenzuron, whereas Turnbull and Howells (1983) showed for crude homogenates of larval integuments from Lucilia that chitin synthesis was inhibited by both polyoxin D and diflubenzuron. However, due to the crude character of the investigated preparations, care has to be taken not to jump to conclusions.…”
Section: Chitin Formationmentioning
confidence: 99%
“…Cohen and Casida (1982), for instance, reported different effects of polyoxins and nikkomycin on chitin synthesis in cecropia moth Hyalophora cecropia and cabbage looper Trichoplusia ni. Mayer et al (1980Mayer et al ( , 1981 observed polyoxin D inhibition in microsomal preparations from Stomoxys only at high concentrations but no inhibitory effect for diflubenzuron, whereas Turnbull and Howells (1983) showed for crude homogenates of larval integuments from Lucilia that chitin synthesis was inhibited by both polyoxin D and diflubenzuron. However, due to the crude character of the investigated preparations, care has to be taken not to jump to conclusions.…”
Section: Chitin Formationmentioning
confidence: 99%
“…Low levels of incorporation of precursors appear to be a characteristic of in vitro studies on chitin synthesis in insects [eg, 3,4,6]. The low levels could be explained by a partial inactivation of a membrane-bound chitin synthase, by the release of inhibitors during preparation of integuments, or by the absence of cofactors.…”
Section: Discussionmentioning
confidence: 99%
“…Although UDP-GlgNAc is the immediate substrate for chitin synthase GlcN and GlcNAc are incorporated into chitin by homogenates from Chironomus cells. This is described also for enzyme preparations from the epidermis of Lucilia cuprinu [33,34]. Whether GlcN and GlcNAc enter the chitin synthesis pathway after acetylation and phosphorylation by enzymes present in the homogenate via UDP-GlcNAc or whether there exists an additiona1 alternative pathway [35] remains unknown.…”
Section: Discussionmentioning
confidence: 99%